1965
DOI: 10.1152/ajplegacy.1965.208.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osmotic diuresis on intrarenal solutes in diabetes insipidus and hydropenia

Abstract: Changes in composition of renal solutes were studied in normal and in diabetes insipidus (D.I.) dogs subjected to varying degrees of solute (mannitol) loading. In both D.I. and hydropenic states, solute loading induced decreases in concentration of medullary solutes, and consequently decreases in corticomedullary gradients of solute concentration. The maximal level of papillary osmolality was associated with excretion of maximally hypertonic urine (nonloaded hydropenic states). The minimal level of papillary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

1966
1966
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Furthermore, the changes in medullary solute composition are not closely related in time or magnitude to those in urinary solute concentrations (present experiments;Goldberg & Ramirez, 1967). We therefore agree with previous suggestions (Appelboom et al 1965;Goldberg & Ramirez, 1967) that the medullary data primarily express the composition of extratubular fluid. To what extent the statistically significant initial inicrease in water content and the non-significant increase in sodium content and decrease in potassium content in the cortex may be attributed to a higher proportion of intratubular fluid is uncertain.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the changes in medullary solute composition are not closely related in time or magnitude to those in urinary solute concentrations (present experiments;Goldberg & Ramirez, 1967). We therefore agree with previous suggestions (Appelboom et al 1965;Goldberg & Ramirez, 1967) that the medullary data primarily express the composition of extratubular fluid. To what extent the statistically significant initial inicrease in water content and the non-significant increase in sodium content and decrease in potassium content in the cortex may be attributed to a higher proportion of intratubular fluid is uncertain.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, within any one slice level changes in the net composition may result from changes in any of these contributory compartments, for example, in intratubular fluid and blood: conversely, redistribution of a constituent between these compartments does not, per se, affect the over-all slice composition. However, not more than about 5 % of medullary tissue is occupied by urine during anti-diuresis in the rat (Bray, 1960b) and not more than about 8 % in osmotic diuresis in the dog (Appelboom et al 1965;Goldberg & Ramirez, 1967). Furthermore, the changes in medullary solute composition are not closely related in time or magnitude to those in urinary solute concentrations (present experiments;Goldberg & Ramirez, 1967).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, urea production and excretion can amount to several hundred millimoles per day. Such large amounts of any other solute, for example mannitol (1,2), would obligate large amounts of water excretion by causing an osmotic diuresis. A basic model of urea handling was proposed by Berliner et al (3), hypothesizing that an osmotic diuresis does not occur with urea because of the accumulation of urea in the inner medullary interstitium, which osmotically balances the high level of urea in the inner medullary collecting duct (IMCD) and urine.…”
mentioning
confidence: 99%
“…The influence of Ca2" on PG synthesis may be mediated through an action of this cation to stimulate the release of free arachidonate (AA) from tissue lipid stores (1), a step which appears to be rate limiting in the cellular generation of PG (4). In the renal IM, where osmolality ordinarily varies over a wide range under normal physiologic conditions (5), there is evidence that solute concentration is an important local determinant of PG synthesis (1,(6)(7)(8). Earlier studies from our laboratory indicated that effects of solute concentration on immunoreactive PGE (iPGE) synthesis, analogous to those of Ca2+, are mediated through alterations in the release of AA from tissue lipid stores (1).…”
Section: Introductionmentioning
confidence: 99%